Adamantan-1-aminium p-toluenesulfonate - Zhang, Yi (International Union of Crystallography, 2011)
There are two unique cations and anions in the asymmetric unit of the title molecular salt, C(10)H(15)NH(3) (+)·C(7)H(7)O(3)S(−). In the crystal, all three hydrogen-bond donors of the protonated amine group make hydrogen-bond interactions with sulfonate O-atom acceptors, linking the cations and anions into chains parallel to the a axis. C—H⋯π interactions are also present.